PENERAPAN TTG MESIN PENGADUK JELADREN DAN RISOPAN JUMBREK DI IKM PACIRAN LAMONGAN - Muhaji, Muhaji (Otopro, 2020)
The purpose of this activity was designed, (1) make and apply a mixer jeladren machine and risopan jumbrek, (2) to improving productivity and jumbrek higine cake. Based on studies conducted in smes and observation, partner smes make jeladren mixer machine with a stinless stell with an electric motor. So are risopan made of plate stainless steel. The outcome of the activities PKM shows that machine mixer jeladren jumbrek and risopan jumbrek physically cunstruction machines and instrument very good, stout, practical. The results of the tryouts machine jeladren mixer jumbrek pointed out once mixer as 10 kg with 12,5 minutes the average time, so as to mixer material 40 pouns  needed time 50 minutes. While  with human resources for mixer 40 pounds of (necessary 8 times mixer in the 200 minutes), thus time mixer 4 times faster. The results of the tryouts risopan jumbrek pointed out in time capable of producing 140 seeds  jumbrek/30 minutes. Increase the result of long with new risopan 5 times.